SER-PROFESSOR: construção de identidade em processo autoformativo - Ferreira, Marília de Abreu (2006)
The purpose of this study was to analyze how the teacher-being narrates and interprets himself/herself as subject in the profession, bearing in mind to comprehend in which way this professional constructs the personal/professional identity, being capable of assuring and of negating himself/herself as a subject inside the schoolsystem. It is a research performed with educators from the first and from the sixth grade of Elementary school from the Public network in São Bernardo do Campo and taking a Master s degree in Education. It was opted to interview six educators, from different teaching areas, turning them into authors of this research. The qualitative methodological approach was used prioritizing the educator narrative. To fulfill this methodology the contributions of Maria Isabel Cunga, Ludke and André; Connelly and Clandini were necessary in order to explain the importance of working with this methodology in the perspective of interpreting and comprehending the building of the teaching identity, mainly, in the line of Educators Formation. The educators formation theme and the identity construction was brought to the light of the studies from Pimenta; Brzezinski; Freire; Vianna; Sung; Nóvoa; Ciampa among others. In the analysis scope, some categories throughout this theme were privileged: reasons that drove to the profession choice; perceptions that the teacher has as subject in the profession; conditions of being a teacher temporarily or being a teacher for life ; building of an identity: conditions of subjecting himself/herself to self-assure as a professional subject. While dealing with these categories and, throughout the research; the perceptions of the teachers were considered as being valuable elements to identify the construction of the teaching identity. These considerations are based on the methodological theoretic support that has great contributions to the theme. From this, relations between Social Psychology and Sociology that enable to identify in the educators narrative one lack of satisfaction towards the system. Some teachers go from the own feeling while narrating all discomfort that the institutions proportionate them; others emphasize in an objective way their daily life, outlining and explaining differences in the condition of being a teacher temporarily or being a teacher for life .